Alterbrassacids A and B: Two Novel Fusicoccane Diterpenoids with Protective Activity Against H2O2-Induced Cardiomyocyte Injury from the Fungus Alternaria brassicicola - Jiang, Rui; Yang, Shenglan; Guo, Jiayi; Jin, Xiaoqi; Wei, Jiangchun; Sun, Weiguang; Guo, Jieru; Zhang, Yonghui; Hu, Zhengxi (Synlett, 2025)
Alterbrassacids A and B, two novel fusicoccane diterpenoids featuring a 5/7/6-fused ring system, along with a known structurally related compound were isolated from fungus Alternaria brassicicola. Their structures, including their absolute configurations, were determined by employing a wide range of spectroscopic analyses, DP4+ probability analyses, and ECD calculations. Preliminary studies showed that alterbrassacid A effectively protected cardiomyocyte H9C2 cells from H2O2-induced lactate dehydrogenase leakage. Furthermore, alterbrassacid A exhibited a significant protective effect on mitochondria by reducing the overproduction of reactive oxygen species and enhancing the mitochondrial membrane potential, highlighting it as a promising cardioprotectant.
Keywords: Alternaria brassicicola; fusicoccane diterpenoids; isolation; structural elucidation; cardiomyocyte protective activity